Correlative Optical and X‐Ray Imaging of Strain Evolution During Double‐Torsion Fracture Toughness Measurements in Shale. Issue 12 (22nd December 2018) - Chandler, Michael R.; Fauchille, Anne‐Laure; Kim, Ho Kyeom; Ma, Lin; Mecklenburgh, Julian; Rizzo, Roberto; Mostafavi, Mahmoud; Marussi, Sebastian; Atwood, Robert; May, Steven; Azeem, Mohammed; Rutter, Ernie; et al.
Abstract: Mode‐I Fracture Toughness, K Ic, was measured in six shale materials using the double‐torsion technique. During loading, crack propagation was imaged both using twin optical cameras, and with fast X‐ray radiograph acquisition. Samples of Bowland, Haynesville, Kimmeridge, Mancos, Middlecliff, and Whitby shales were tested in a range of orientations. The measured fracture toughness values were found to be in good agreement with existing literature values. The two imaging techniques improve our understanding of local conditions around the fracture‐tip, through in situ correlation of mechanical data, inelastic zone size, and fracture‐tip velocity. The optical Digital Image Correlation technique proved useful as a means of determining the validity of individual experiments, by identifying experiments during which strains had developed in the two "rigid" specimen halves. Strain maps determined through Digital Image Correlation of the optical images suggest that the scale of the inelastic zone is an order of magnitude smaller than the classically used approximation suggests. This smaller damage region suggests a narrower region of enhanced permeability around artificially generated fractures in shales. The resolvable crack‐tip was tracked using radiograph data and found to travel at a velocity around 470 μm/s during failure, with little variation in speed between materials and orientations. Fracture pathways in the bedding parallel orientations were observed to deviate from linearity, commonly following layer boundaries. This suggests that while a fracture traveling parallel to bedding may travel at a similar speed to a bedding perpendicular fracture, it may have a more tortuous pathway, and therefore access a larger surface area. Plain Language Summary: Fracture toughness is a measure of the strength of a material, in the presence of existing flaws or cracks. Here fracture toughness was measured in six shale materials with fractures oriented both parallel and perpendicular to the bedding layers in the shales. During the experiments, the progressing fractures were imaged using both optical cameras and radiographs recorded using a synchrotron. The radiograph images were used to track the velocity of the progressing fracture, which did not vary strongly with different materials or orientations. The optical images were used to characterize the "damage zone" around the main fracture in which microfractures develop. This region was seen to be much smaller than conventional models suggest, which could imply that the developing fractures increase permeability over a much narrower region than previously believed. Key Points: Double‐torsion fracture toughness measurements were made in six shale materials Optical digital image correlation was used to determine strain fields, and suggests an extremely small yielding zone Radiograph imaging was used to track the fracture‐tip velocity and crack‐mouth opening displacement